Endemic flowers of the chimborazo province as a source of inspiration for texture generation (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The Chimborazo Province in Ecuador is home to a rich biodiversity of endemic flora adapted to its extreme conditions. This article examines how local floristic species, including the Chuquiraguaand the Soya de los Andes, can inspire the creation of textures applied to design. Through bibliographic review and visual study, unique patterns and colors were identified in these plants. When deconstructed and abstracted, they generate textures that reflect cultural and natural identity. The research highlights the importance of integrating natural and cultural elements into design, promoting sustainable and meaningful solutions that preserve Chimborazo's natural heritage.
Keywords: Endemic flora; morphology; syntax; textures